Factors Associated with Adverse Neonatal Outcome in Singleton Pregnancy: A Hospital Based Case-Control Study - Jesmin, Suha; Rijvi, Shiffin; Sengupta, Ruma (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: One of the sustainable development goals for 2030 is to reduce infant mortality. Unfavourable birth outcomes are the main cause of infant morbidity and mortality. This study looked into the factors associated with adverse foetal outcomes in Bangladesh. Methods: The case-control study was conducted in BIRDEM general Hospital over 210 singleton pregnant women following 1975 Helsinki declaration and its later amendment. Cases (n=105) were considered as having any adverse birth outcome, while controls (n=105) had none of the adverse birth events. Data were recorded in separated case-record form and analyzed by SPSS-24. Results: Mean age of cases and controls were 28.98±5.48 (SD) years and 28.65±4.65 years, respectively (p=0.635). Preterm labour (64.8%), low birth weight (LBW, 41.9%) and neonatal intensive care unit (NICU) admission (31.4%) were the common adverse outcomes. Cases had significantly higher prevalence of obesity (24.8% vs 13.3%, p=0.035), gestational diabetes mellitus (49.5% vs 33.3%, p=0.017), pregnancy-induced hypertension (PIH, 40% vs 17.1%, p<0.001) and premature rupture of membrane (PROM, 15.2% vs 4.8%, p=0.011). Maternal age >35 years (adjusted odds ratio=3.77, 95%CI=1.12-12.65), PIH (AOR=3.602, 95%CI=1.7977.22), and PROM (AOR=5.74, 95%CI=1.83-18.00) were the significant risk factors for adverse foetal outcome. Besides, PIH had significant odds ratio for preterm labour (AOR=2.21, 95%CI=1.13-4.33), LBW (AOR=4.19, 95%CI=1.93-9.12) and NICU (AOR=8.93, 95%CI=3.7321.38). Maternal age >35 years (AOR=3.21, 95%CI=1.04-9.88) and PROM (OR=3.65, 95%CI=1.18-11.3) were associated with LBW, while previous caesarian section (CS) was responsible for preterm labour (AOR=2.298, 95%CI=1.09-4.87). Conclusion: Pregnancy with advance maternal age, PIH, previous CS and PROM were the determinants of adverse birth outcomes. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 32-38